Comparison between two methods of codified education, and no codified education on knowledge and attitude of chronic mental patients for acceptance of therapy regimen - kerman Saravi F (Iran University of Medical Sciences, 1999)
This is a quasi-experimental study. The purpose was to comparison between two methods of codified education, and no codified education on knowledge and attitude of chronic mental patients for acceptance of therapy regimen. The hypothesis was patients participated in codified educational classes have more knowledge and positive attitude in compare to patients participated in no codified educational classes. A sample of 60 mental patients with the history of at least 8 year of mental diseases selected randomly. Data gathered by a questionnaire before and after education. The statistical test used was analysis of variance. Results showed that there were no significant statistical differences between mean score of knowledge and attitude before and after education. Then the hypothesis rejected.